Rekonstruksi Hukum Harta Bersama dalam Perkawinan - Widya Sari; Muhammad Arif (LPPM Universitas Ekasakti Padang, 2023)
This paper aims to examine the potential for disputes in the problem of joint property in marriage. Normatively, both Article 85 KHI and 86 paragraph 1 KHI and Article 171 letter e KHI have the potential for turbulence of law which has implications for social turbulence which leads to legal uncertainty itself. This research is a literature study (library research) with the data analysis method used is content analysis. The results of this study indicate that the legal norms contained in Article 85 KHI and 86 paragraph 1 KHI, as well as Article 171 letter e KHI, basically require an agreement as a form of manifestation of separation, possession of marital assets and legal actions that can be performed each party over their respective assets without neglecting their respective obligations in marriage, so that with an agreement on marital assets, the clustering of assets controlled by each party both on innate assets, gifts, inheritance and assets acquired by each party during the marriage become a stressing point in minimizing the potential for disputes while at the same time providing legal certainty when disputes occur both during the divorce phase and the death phase of one of the parties